Sample Preparation for Mass Spectrometry Imaging of Plant Tissues: A Review - Dong, Yonghui; Li, Bin; Malitsky, Sergey; Rogachev, Ilana; Aharoni, Asaph; Kaftan, Filip; Svatoš, Aleš; Franceschi, Pietro (Frontiers in Plant Science, 2016)
Mass spectrometry imaging (MSI) is a mass spectrometry based molecular ion imaging technique. It provides the means for ascertaining the spatial distribution of a large variety of analytes directly on tissue sample surfaces without any labeling or staining steps. These advantages make it an attractive molecular histology tool in medical, pharmaceutical and biological research. Likewise, MSI has started gaining popularity in plant sciences; yet, information regarding sample preparation methods specific for plant tissues is still limited. Sample preparation is a crucial step that is directly associated with the quality and authenticity of the imaging results, it therefore demands in-depth studies based on the characteristics of plant samples. In this review, a sample preparation pipeline is discussed in detail and illustrated through selected practical examples. In particular, special concerns regarding sample preparation for plant imaging are critically evaluated. Finally, the applications of various MSI techniques in plants are reviewed according to different classes of plant metabolites.